Unexpected Transcripts in Tn7 orf19.2646 C. albicans Mutant Lead to Low Fungal Burden Phenotype In vivo - Pierrehumbert, Aude; Ischer, Françoise; Coste, Alix T. (Frontiers in Microbiology, 2017)
The commensal fungus Candida albicans is the major cause of fungal systemic infection in immuno-compromised patients, with a mortality rate approaching 50 % in the case of bloodstream infections. There is therefore a clear need to better understand fungal biology during infection to improve treatment. One of the particularities of C. albicans is its capacity to adapt to drastically diverse environments such as brain, bloodstream or gut. Adaptations to environmental change are mediated by transcription factors (TF) that modulate the expression of their target genes. Previous screening of a collection of Tn7 C. albicans TF mutants in vivo identified orf19.2646 as playing a crucial role in the ability of the fungus to survive within its host. Indeed, the orf19.2646 Tn7 interruption mutant strain displayed a reduced fungal burden compared to the wild-type strain. Surprisingly, an independent deletion mutant did not recapitulate the phenotype of the Tn7 interruption mutant. In the present study, we therefore investigated the difference between these two mutants and determined by performing a RACE analysis whether unexpected transcripts of the Tn7 mutant occurred. We found that two such transcripts upstream and downstream of the Tn7 insertion site were produced. The two transcripts were expressed in an orf19.2646 deletion mutant which displayed a significantly reduced fungal burden level compared to the wild-type in G. mellonella. When the regions corresponding to these transcripts were deleted in the Tn7 mutants, the strains lacking both regions displayed a fungal burden similar to that of the wild-type strain. This study shows for the first time that mRNA transcription may occur downstream of a Tn7 sequence. In addition, these results demonstrated that the low fungal burden phenotype observed in the orf19.2646 Tn7 mutant is due to the presence of these two transcripts together participating to an unidentified virulence mechanism to be further elucidated.